New technologies reduce greenhouse gas emissions from nitrogenous fertilizer in China - Zhang, Wei-Feng; Dou, Zheng-Xia; He, Pan; Ju, Xiao-Tang; Powlson, David; Chadwick, Dave; Norse, David; Lu, Yue-Lai; Zhang, Ying; Wu, Liang; Chen, Xin-Ping; Cassman, Kenneth G.; et al. (National Academy of Sciences, 2013)
Synthetic nitrogen (N) fertilizer has played a key role in enhancing food production and keeping half of the world’s population adequately fed. However, decades of N fertilizer overuse in many parts of the world have contributed to soil, water, and air pollution; reducing excessive N losses and emissions is a central environmental challenge in the 21st century. China’s participation is essential to global efforts in reducing N-related greenhouse gas (GHG) emissions because China is the largest producer and consumer of fertilizer N. To evaluate the impact of China’s use of N fertilizer, we quantify the carbon footprint of China’s N fertilizer production and consumption chain using life cycle analysis. For every ton of N fertilizer manufactured and used, 13.5 tons of CO 2 -equivalent (eq) (t CO 2 -eq) is emitted, compared with 9.7 t CO 2 -eq in Europe. Emissions in China tripled from 1980 [131 terrogram (Tg) of CO 2 -eq (Tg CO 2 -eq)] to 2010 (452 Tg CO 2 -eq). N fertilizer-related emissions constitute about 7% of GHG emissions from the entire Chinese economy and exceed soil carbon gain resulting from N fertilizer use by several-fold. We identified potential emission reductions by comparing prevailing technologies and management practices in China with more advanced options worldwide. Mitigation opportunities include improving methane recovery during coal mining, enhancing energy efficiency in fertilizer manufacture, and minimizing N overuse in field-level crop production. We find that use of advanced technologies could cut N fertilizer-related emissions by 20–63%, amounting to 102–357 Tg CO 2 -eq annually. Such reduction would decrease China’s total GHG emissions by 2–6%, which is significant on a global scale.